Historic logbooks reveal spatial footprints of commercial whaling - Nicholas A. Freymueller; Eline D. Lorenzen; Matthew Ayre; Kit M. Kovacs; Christian Lydersen; Carsten Rahbek; Damien A. Fordham (Proceedings of the National Academy of Sciences, 2026)
Commercial harvesting of bowhead whales ( Balaena mysticetus ), primarily by British and American whalers during the late-1700s to early-1900s, nearly caused their extinction. While whaling-offtake rates during this period are known, their spatiotemporal footprints are not, creating an important gap in understanding of the species recovery patterns. Using archival logbooks and Bayesian modeling, we reconstructed daily positions for >700 whaling voyages (totaling >90,000 d) across the Arctic, revealing spatiotemporal patterns and causal drivers of these seafaring routes and their hunting successes. We find that whaling operations by British and American whalers expanded rapidly throughout the Arctic, moving in predictable ways through hazardous sea ice conditions, reaching all but the most remote bowhead whale habitats within a century. Extensive sea ice cover formed barriers, delaying access to some profitable whaling grounds and suppressing harvest intensity. These fine-scale processes created important population refugia across the Arctic, forming a network of naturally “protected areas” where cumulative harvest impacts were minimized. Our analyses show that these refugia were larger and persisted longer in bowhead whale populations that are recovering faster today, indicating that modern recovery patterns are likely tied to the spatial patterns of past exploitation.